Frontotemporal Dementia, Manifested as Schizophrenia, with Decreased Heterochromatin on Chromosome 1 - Gourzis, Philippos; Skokou, Maria; Polychronopoulos, Panagiotis; Soubasi, Evanthia; Triantaphyllidou, Irene-Eva; Aravidis, Christos; Sarela, Antonia-Ioanna; Kosmaidou, Zoe (Case Reports in Psychiatry, 2012)
Introduction. Frontotemporal dementia is a disorder of complex etiology, with genetic components contributing to the disease. The aim of this report is to describe a young patient suffering from frontotemporal dementia, misdiagnosed as schizophrenia, related to a genetic defect on chromosome 1. Case Presentation. A 29-year-old female patient, previously diagnosed as having schizophrenia, was hospitalized with severe behavioural disturbances. She demonstrated severe sexual disinhibition, hyperphagia, lack of motivation, apathy, psychotic symptoms, suicidal thoughts, and cognitive deterioration. Focal atrophy of frontal and anterior temporal structures bilaterally was found on brain MRI, as well as bifrontal hypo perfusion of the brain on SPECT scan. The diagnosis of frontotemporal dementia was made clinically, according to Lund and Manchester groups and Neary diagnostic criteria. Chromosomal analysis was conducted and revealed decrease in length of heterochromatin on the long arm of chromosome 1 (46, XX, 1qh-). Parental karyotypes were normal. Discussion. Frontotemporal dementia, and particularly early-onset cases, can be often misdiagnosed as schizophrenia, with negative impact on case management. Genetic testing could be an aid to the correct diagnosis, which is crucial for optimal patient care.